Analisis Pengaruh Rasio Profitabilitas Terhadap Harga Saham Di Perusahaan Manufaktur(Studi Kasus Pada Perusahaan Food and Beverages dan Consumers Goods yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Wahyuni, Sri; , Basworo Dibyo, S.E, M.Si (2017)
The purpose of this study to analyze the effect of Return On Assets (ROA), Return on Equity (ROE), Debt To Equity Return (DER), Earning Per Share (EPS) and Net Profit Margin (NPM) on stock price of companies listed on Indonesia Stock Exchange in 2011-2014. The data used are secondary data from company financial statements derived from the annual report. Determination of sample using purposive sampling method based on certain criteria. From this method the company acquired 17 food and beverages and consumers goods that meet the established criteria. The amount of data used for research as much as 68 with a 4 year study period. Data analysis method using multiple linear analysis. Testing the hypothesis in this study using a t test to determine the independent variables partially. While the F-test, used to determine the influence of the independent variable is ROA, ROE, DER, EPS, and NPM on stock prices simultaneously. Regression coefficient test used in this study to determine how much influence the independent variables in explaining the dependent variable. Based on the partial results of the study note that the DER does not significantly and positive influence stock prices. ROA, ROE, and EPS significant effect and positive on stock prices. NPM significant effect and negative on stock prices. While simultaneously ROA, ROE, DER, EPS, and NPM significant effect and positive on stock prices. Variable stock price can be explained by the variable ROA, ROE, DER, EPS, and NPM amounted to 85.3% and the remaining 14.7% is explained by other variables.